2011
DOI: 10.1111/j.1346-8138.2010.01139.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitiligo: A review of the published work

Abstract: Vitiligo is a common depigmenting skin disorder, characterized by acquired, idiopathic, progressive, circumscribed hypomelanosis of the skin and hair, with total absence of melanocytes microscopically. It occurs worldwide, with an incidence rate of between 0.1% and 2%. Vitiligo is an important skin disease having a major impact on the quality of life of the patient suffering from it. The causes of this condition are uncertain but seem to be dependent on the interaction of genetic, immunological and neurologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
183
1
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(196 citation statements)
references
References 104 publications
3
183
1
9
Order By: Relevance
“…Vitiligo is categorized as a depigmentation disorder, where the loss of active melanocytes causes the appearance of white patches on the skin ( Whitton et al,2008 ;Yaghoobi et al, 2011b). These patches are of various sizes and shapes.…”
Section: Clinical Manifestation Of Vitiligomentioning
confidence: 99%
See 1 more Smart Citation
“…Vitiligo is categorized as a depigmentation disorder, where the loss of active melanocytes causes the appearance of white patches on the skin ( Whitton et al,2008 ;Yaghoobi et al, 2011b). These patches are of various sizes and shapes.…”
Section: Clinical Manifestation Of Vitiligomentioning
confidence: 99%
“…It has been introduced based on its visual phenotype (Yaghoobi et al, 2011a,b; as cited in Birlea et al, 2008;. Studies have shown that approximately 20% of vitiligo patients have at least one first-degree relative with this disorder; so, it seems that the relative risk for first-degree relatives of vitiligo patients is increased by 7-to 10-fold (Wolff et al, 2007;Yaghoobi et al, 2011b). Only a few vitiligo susceptibility genes have been introduced with certainty.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed pathogenesis of vitiligo relates to genetics, neurochemical factors, self-destruction of melanocytes and autoimmunity, etc. [1]. The fact that there are roughly patterned clinical distributions of vitiligenous lesions that conforms to different clinical types of vitiligo suggest different etiological or pathophysiological pathways involved in the disease.…”
Section: Introductionmentioning
confidence: 99%
“…It occurs worldwide, with an incidence of 0.5% to 2.0%. 1 Vitiligo is disfiguring in all races but particularly more so in dark skinned people because of strong contrast. 2 Vitiligo may entail significant psychosocial consequences.…”
Section: Introductionmentioning
confidence: 99%
“…It occurs worldwide, with an incidence of 0.5% to 2.0%. 1 Vitiligo is disfiguring in all races but particularly more so in dark skinned people because of strong contrast.2 Vitiligo may entail significant psychosocial consequences. Vitiligo is a social stigma and is associated with a decreased quality of life, especially when lesions are located over the face; thus, it may affect the quality of social and personal life depending on the patient's perception.…”
mentioning
confidence: 99%